Digitally enhanced consumer packaged goods: a data-inspired ideation approach - Berumen Salazar, Jose Gustavo (2022)
Consumer packaged goods (CPG) are disposable, relatively low-price, frequently-purchased products such as a bottle of milk or a bar of chocolate. CPGs have a pervasive presence in our everyday practices, and a number of instances have shown the potential of integrating their existing functionalities into the Internet of Things (IoT). Such innovations as, for example, a pill container which reminds one when to take their medication, or a disposable toothbrush which teaches children about oral hygiene, illustrate the capacity of digitally enhanced CPGs to have a positive impact in countless aspects of our lives. However, despite recent research in human-computer interaction (HCI) aimed specifically at enhancing interactions with CPGs, devising enhanced versions of these goods which meet people's needs and reflect their values remains quite elusive. Many challenges in the design of enhanced CPGs stem from their defining characteristics, including their disposability and frequent need to be replenished, as well as from the fact that they are rarely used in isolation, but rather in conjunction with one another as sets.